Islam, an American religion - Marzouki, Nadia; Delogu, Christopher Jon (New York : Columbia University Press, 2017)
Islam: An American Religion demonstrates how Islam as formed in the United States has become an American religion in a double sense--first through the strategies of recognition adopted by Muslims and second through the performance of Islam as a faith. Nadia Marzouki investigates how Islam has become so contentious in American politics. Focusing on the period from 2008 to 2013, she revisits the uproar over the construction of mosques, legal disputes around the prohibition of Islamic law, and the overseas promotion of religious freedom. She argues that public controversies over Islam in the United States primarily reflect the American public's profound divisions and ambivalence toward freedom of speech and the legitimacy of liberal secular democracy.
Frontmatter -- Contents -- Foreword -- Acknowledgments -- Introduction to the American Edition: A Euro-American Debate Over Islam -- Introduction -- 1. Muslim Americans: A Religious Minority Like Any Other? -- 2. The Mosque Controversies: Moral Offense and Religious Liberty -- 3. The Anti-Sharia Movement -- 4. The Face of Anti-Muslim Populism -- 5. Forcing the First Amendment: American Exporting of Religious Freedom -- Conclusion -- Notes -- Selected Bibliography -- Index.
Includes bibliographical references and index.
In English.
Online resource; title from digital title page (viewed on January 10, 2018).
Added to collection customer.56279.3
Keywords: Islam -- Social aspects -- United States; Islam and politics -- United States; Islamophobia -- United States; RELIGION -- Islam -- General; Islam and politics; Islam -- Social aspects; Islamophobia; United States; Electronic books